Epidemiological Genomics of Klebsiella pneumoniae isolates from hospitals across Colombia - Victor A. Medina; Angela S. García-Vega; Fernando Rodríguez; Enmanuel S. Triviño-García; Jaime A. Robledo; Aura L. Leal; Julián C. Galvis; Luis F. Reyes; Genomic Epidemiology of Antimicrobial Resistance Consortium (GEAR); Iruka N. Okeke; Natacha Couto; Emmanuelle A. Kumaran; et al. (npj Antimicrobials and Resistance)
Abstract Klebsiella pneumoniae is one of the most important nosocomial pathogens worldwide. In Colombia, K. pneumoniae has been identified as the second most frequent microbial etiologic agent of healthcare-associated infections. We conducted a prospective local study of 335 K. pneumoniae isolates in 26 nationwide hospitals from 2020 to 2021. We found that the spread of carbapenem resistance was mediated by successful clones belonging to sequence types (ST) such as ST11, ST1082, and ST307, related to intra-hospital infections. We observed that bla KPC remains the primary resistance mechanism to carbapenems and that, unlike other countries, ST11 strains commonly carry bla KPC-3. We identified the recent introduction and circulation of new sequence types with different resistance mechanisms and hypervirulence. Besides, we detected possible transmission events closely linked to carbapenemase-carrying strains, mainly in intensive care units. This study helps us understand how K. pneumoniae disseminates in Colombian hospitals and where to direct effective intervention measures.